Transformation of standard models of antonimization of words in the works of A.P. Chekhov - Wierzbiński, Jarosław (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
The article discusses the functioning of uncorrelated antonyms in the sphere of concepts in Anton Chekhov’s works. This type of lexical contrasts occurs when characterized objects or phenomena that refer to different concepts are not compatible. Traditional oppositions of polysemic units refer to the same objects, e.g. the term хороший – плохой when assessing someone (employee skills, the artistry of a writer), or something (a work, a script). When the semems of such polysemic units cross, they characterize different objects, e.g. “иногда в плохих стихах узнаешь хорошего автора-человека,” where the term плохой refers to a poem and хороший refers to its author. Such opposition differs from dictionary antonyms, which makes it more expressive and original given the shaping of statements in literary texts. The conducted analysis proves that in Chekhov’s literary works the field of antonymic contacts is expanded to include various innovations, which is primarily an artistic measure and largely testifies to the specificity of the writer’s idiolect.